Studies an mononuclear chelates derived from substituted Schiff base ligands (Part 4):Synthesis and characterization of a new 5-hydroxysalicyliden-P-aminoacetophenoneoxime and its complexes with Co(II),Ni(II),Cu(II) and Zn(II) - Canpolat, Erdal; Kaya, Mehmet Demir (My University, 2005)
5-Hydroxysalicyliden-p-aminoacetophenoneoxime (LH) was synthesized starting from p-aminoacetophenoneoxime and 5-hydroxysalicylaldehyde. Complexes of this ligand with $Co^{+2}$, $Ni^{+2}$, $Cu^{+2}$ and $Zn^{+2}$ salts were prepared. With this ligand, complexes were synthesized using $Co^{+2}$, $Ni^{+2}$, $Cu^{+2}$ and $Zn^{+2}$ salt with a metal:ligand ratio of 1:2. Their structures were elucidated on the basis of elemental analyses, IR, $^1H$- and $^{13}C$-NMR, electronic spectra, magnetic susceptibility measurements, molar conductivity and thermogravimetric analyses.
Keywords: Kimya; Tıbbi; Toksikoloji; Farmakoloji ve Eczacılık